2018
DOI: 10.17265/2161-6256/2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Watermelon mosaic virus Isolate Inducing a Severe Disease in Watermelon in Saudi Arabia

Abstract: In one of the field visits to cucurbits-growing areas in vicinity of Riyadh city during 2013-2015, severe virus disease-like symptoms were observed on watermelon in Al-Ammariyah area. Mechanical inoculation of the different plant species used in the host range study, from the collected symptomatic watermelon samples, produced mosaic symptoms on Citrullus lanatus, Cucumis sativus, Cucurbita pepo, C. melo, C. melo subsp. melo and Nicotiana benthamiana, but chlorotic local lesions on Chenopodium amaranticolor. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Common symptoms of cucurbit-related WMV infections were well-documented in many agroecosystems worldwide. Similar symptoms as in this study have also been reported in New Zealand from buttercup squash (Fletcher et al, 2000), watermelon in Saudi Arabia (Santosa et al, 2018), cucurbitaceous vegetables in the Czech Republic (Svoboda and Hale, 2011), cucurbit crops in USA and southern United States (Fernandes et al, 1991;Ali et al, 2012), watermelons and pumpkins in Uganda (Masika et al, 2017).…”
Section: Figure 2 Dna Fragments Of Watermelon Mosaic Potyvirus Amplif...supporting
confidence: 89%
“…Common symptoms of cucurbit-related WMV infections were well-documented in many agroecosystems worldwide. Similar symptoms as in this study have also been reported in New Zealand from buttercup squash (Fletcher et al, 2000), watermelon in Saudi Arabia (Santosa et al, 2018), cucurbitaceous vegetables in the Czech Republic (Svoboda and Hale, 2011), cucurbit crops in USA and southern United States (Fernandes et al, 1991;Ali et al, 2012), watermelons and pumpkins in Uganda (Masika et al, 2017).…”
Section: Figure 2 Dna Fragments Of Watermelon Mosaic Potyvirus Amplif...supporting
confidence: 89%
“…Ten minutes after mechanical inoculation, the plants were rinsed with distilled water to remove buffer and carborundum. Plants were maintained at 25 -27 °C and observed for symptoms expression for a period of four to five weeks (Santosa et al, 2018).…”
Section: Hosts Indexingmentioning
confidence: 99%